Hospitalizations for acetaminophen overdose: a Canadian population-based study from 1995 to 2004 - Fong Andrew; Li Bing; Myers Robert P; Shaheen Abdel; Quan Hude (BMC, 2007)
Abstract Background Acetaminophen overdose (AO) is the most common cause of acute liver failure. We examined temporal trends and sociodemographic risk factors for AO in a large Canadian health region. Methods 1,543 patients hospitalized for AO in the Calgary Health Region (population ~1.1 million) between 1995 and 2004 were identified using administrative data. Results The age/sex-adjusted hospitalization rate decreased by 41% from 19.6 per 100,000 population in 1995 to 12.1 per 100,000 in 2004 (P < 0.0005). This decline was greater in females than males (46% vs. 29%). Whereas rates fell 46% in individuals under 50 years, a 50% increase was seen in those ≥ 50 years. Hospitalization rates for intentional overdoses fell from 16.6 per 100,000 in 1995 to 8.6 per 100,000 in 2004 (2004 vs. 1995: rate ratio [RR] 0.49; P < 0.0005). Accidental overdoses decreased between 1995 and 2002, but increased to above baseline levels by 2004 (2004 vs. 1995: RR 1.24;P < 0.0005). Risk factors for AO included female sex (RR 2.19; P < 0.0005), Aboriginal status (RR 4.04; P < 0.0005), and receipt of social assistance (RR 5.15; P < 0.0005). Conclusion Hospitalization rates for AO, particularly intentional ingestions, have fallen in our Canadian health region between 1995 and 2004. Young patients, especially females, Aboriginals, and recipients of social assistance, are at highest risk.